Advancing precision medicine with personalized drug screening. Issue 1 (January 2019) - Gorshkov, Kirill; Chen, Catherine Z.; Marshall, Raisa E.; Mihatov, Nino; Choi, Yong; Nguyen, Dac-Trung; Southall, Noel; Chen, Kevin G.; Park, John K.; Zheng, Wei
Highlights: Personalized drug screening (PDS) using patient-derived cells and approved drugs predicts drug efficacy in vitro before drug treatment in patients. This 'bedside to bench and back to patient' practice is a collaborative effort between basic researchers and clinicians. Personalized drug screening combined with personalized genomic analysis can contribute greatly to development of future precision medicine. The infrastructure and technologies need to be further developed for implementation of personalized drug screening in the clinical setting. Abstract : Personalized drug screening (PDS) of approved drug libraries enables rapid development of specific small-molecule therapies for individual patients. With a multidisciplinary team including clinicians, researchers, ethicists, informaticians and regulatory professionals, patient treatment can be optimized with greater efficacy and fewer adverse effects by using PDS as an approach to find remedies. In addition, PDS has the potential to rapidly identify therapeutics for a patient suffering from a disease without an existing therapy. From cancer to bacterial infections, we review specific maladies addressed with PDS campaigns. We predict that PDS combined with personal genomic analyses will contribute to the development of future precision medicine endeavors.